Kodeks Basilicanus A. 6 (alias e) a rodzina „Q” rękopiśmiennego przekazu "Vita Sancti Pauli Primi Eremitae" św. Hieronima - Degórski, Bazyli (Vox Patrum, 2011)
The essay aims at continuing and completing our previous research concerning the manuscript tradition of the Vita Sancti Pauli Primi Eremitae of St. Jerome. The Basilicanus A.6 (alias E) manuscript, kept in the Vatican Apostolic Library (Archives of the Chapter of St. Peter’s in the Vatican), contains the whole text of the Vita Sancti Pauli Primi Eremitae of St. Jerome – though A. Poncelet places it among the unfinished manuscripts of the works of St. Jerome, while neither J.F. Cherf nor W.A. Oldfather make mention of it. The Basilicanus A. 6 (alias E) manuscript belongs to the „Q” family of the manuscript tradition of the Vita Sancti Pauli Primi Eremitae, established by J.F. Cherf, insofar as it possesses all the variations which are shared solely by the manuscripts codes belonging to this group. On a more technical level, this manuscript belongs to the first subgroup of the „Q” family, since it shares with it all the specific variations. As far as the manuscripts constituting the subgroup of the „Q” family are concerned, the Basilicanus A. 6 is more closely linked to the Vaticanus Latinus 1194 code rather than with the two remaining codes of the subgroup, namely the Vaticanus Latinus 5772 and the Vaticanus Latinus 6075. Nevertheless, the Basilicanus A. 6 cannot directly derive from the Vaticanus Latinus 1194, because it does not always coincide with it, and because it presents some meaningful additions, which are not found in the Vaticanus Latinus 1194.